Stage mothers : women, work, and the theater, 1660-1830 - Engel, Laura; McGirr, Elaine M., 1972- (Transits (Bucknell University), 2014)
Stage Mothers expands the discussion of eighteenth-century women's social and dramatic roles by demonstrating the complicated, contradictory, and celebratory faces of maternity on stage and on the page. This collection examines and extends recent debates in women's history, theater history, and eighteenth-century literature and drama.